(untitled) (IAHS Medical Journal, 2024)
Background: Tetanus Toxoid (TT) is a substance that is derived from the toxin released by bacterium that causes the disease tetanus. It is used as a vaccine to prevent tetanus or to help boost the immune response to other vaccines. This study aimed to evaluate pregnant women’s knowledge and immunization status regarding Tetanus Toxoid (TT) vaccination in rural Bangladesh. Materials and methods: A cross-sectional survey was conducted among 53 conveniently selected respondents using a mixed-type questionnaire. Results: The study found that 94.34% of the respondents had knowledge about TT vaccination, but only 56.6% had received the vaccine. Of those who received the vaccine, only 10% completed five doses of TT vaccination, and 63% received three doses. The study revealed that TT vaccination coverage was higher in the upper class and lower in very poor families. Conclusion: The study concludes that the TT vaccination status is not satisfactory, more efforts are needed to improve vaccination coverage. Government, non-governmental organizations, donor agencies and the mass media can play a significant role in raising awareness and improving healthcare delivery. IAHS Medical Journal Vol 6(1), June 2023; 50-52